2016
DOI: 10.1155/2016/1539096
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cognitive Improvement in Alcohol-Dependent Inpatients Using the Montreal Cognitive Assessment (MoCA) Score

Abstract: Background. Cognitive dysfunction is a common feature in alcohol use disorders. Its persistence following alcohol detoxification may impair quality of life and increase the risk of relapse. We analyzed cognitive impairment changes using the Montreal Cognitive Assessment (MoCA) score in a large sample of alcohol-dependent inpatients hospitalized for at least 4 weeks. Method. This was an observational longitudinal survey. Inclusion criteria were alcohol dependence (DSM-IV) and alcohol abstinence for at least one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 39 publications
4
21
0
1
Order By: Relevance
“…By considering the best balance between sensitivity and specificity, the cutoff score fell to 26 for uncorrected scores, that is, the same as that proposed for the detection of mild cognitive impairment (Nasreddine et al., ). As we used this cutoff in our previous studies, this confirms a posteriori the reliability of our results on the prevalence of cognitive impairment in alcoholics (Alarcon et al., ; Pelletier et al., ).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…By considering the best balance between sensitivity and specificity, the cutoff score fell to 26 for uncorrected scores, that is, the same as that proposed for the detection of mild cognitive impairment (Nasreddine et al., ). As we used this cutoff in our previous studies, this confirms a posteriori the reliability of our results on the prevalence of cognitive impairment in alcoholics (Alarcon et al., ; Pelletier et al., ).…”
Section: Discussionsupporting
confidence: 86%
“…In a previous work, we evaluated the interest of MoCA administration in a large series of patients with AUD (Alarcon et al., ) and concluded that MoCA is an appropriate tool for detecting cognitive impairment in that population. We then showed that MoCA was a useful tool for measuring changes in cognitive performance in alcohol‐dependent inpatients (Pelletier et al., ). However, in these papers, we interpreted our results according to published data obtained in patients with neurological diseases unrelated to alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations